The Implementation Analysis Related To The Prevention Of Hepatitis B Disease Among Health Workers In Lebong Regency In 2025 - Rachman Rachman; Hartian Pansori; Tuti Rohani (Journal of International Public Health, 2026)
The Data from WHO in 2019 estimated that 296 million people live with chronic hepatitis B infection, with 1.5 million new infections occurring each year, leading to approximately 820,000 deaths. The transmission of this virus primarily occurs through contact with infected blood or bodily fluids, placing health workers at high risk of contracting Hepatitis B. Hepatitis B vaccination coverage among health workers remains low, below 60%. This study aims to analyze the factors influencing the transmission of hepatitis B infection among health workers in Lebong Regency. The method used in this study is quantitative research with a cross-sectional approach, and its statistical analysis employs Chi-Square and logistic regression analysis. Among all observed variables that showed a statistical relationship (P<0.05) are immunization status, use of Personal Protective Equipment (PPE), implementation of standard operating procedures (SOP), and behavior (p <0.05). The results of the bivariate analysis using the Chi-square statistical test (continuity correction) yielded asymptotic significance (p) values of 0.001, 0.002, 0.013, and 0.046. The second analysis results indicated that the variables of immunization status (p value=0.002), use of PPE (p value=0.006), implementation of SOP (p value=0.059), and behavior (p value=0.017) were significant, with immunization status having the smallest p value (Sig) of 0.002. From the analysis, an Odds Ratio (OR) of 5.606 was obtained, indicating that immunization status has a 5.606 times greater chance of hepatitis B occurrence among health workers. Based on the results of this study, program holders should evaluate the planning and implementation of vaccination programs, ensuring that health workers in healthcare facilities receive Hepatitis B immunization.